2003
DOI: 10.1016/s1286-4579(03)00149-7
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of the presence of Seoul virus in Cambodia

Abstract: A study was conducted in agricultural and urban areas in Cambodia to assess the presence of hantaviruses in rodent populations. In 1998, rodents were trapped in two villages and in Phnom Penh city around market places and a rubbish dump. IgG antibodies to Hantaan virus were detected in 54 (8.2%) rodents among 660 tested: 6.4% (13/203) among roof rats (Rattus rattus), 20.9% (39/187) among Norway rats (R. norvegicus), 16.7% (2/12) among unidentified Rattus species and none in 183 Polynesian rats (R. exulans) or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
44
1
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(49 citation statements)
references
References 8 publications
3
44
1
1
Order By: Relevance
“…This phylogenetic analysis was also performed with a reduction of the S CDS dataset to 519 nucleotides (positions 364-882). This allowed the inclusion of the sequences of Cambodian strains close to THAIV, and of other THAIV sequences (Reynes et al 2003, Hugot et al 2006, Blasdell et al 2011. Although the tree topology changed slightly and the statistical support was lower, all sequences grouped together (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This phylogenetic analysis was also performed with a reduction of the S CDS dataset to 519 nucleotides (positions 364-882). This allowed the inclusion of the sequences of Cambodian strains close to THAIV, and of other THAIV sequences (Reynes et al 2003, Hugot et al 2006, Blasdell et al 2011. Although the tree topology changed slightly and the statistical support was lower, all sequences grouped together (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Thailand virus species include THAIV associated with the rodent Bandicota indica in Thailand, as well as Serang and Jurong variants and an unnamed variant, all associated with R. tanezumi in Indonesia, Singapore, and Cambodia, respectively (Elwell et al 1985, Reynes et al 2003, Hugot et al 2006, Plyusnina et al 2009, Johansson et al 2010. The presence of a THAIV variant in Madagascar, amazingly far from South and Southeast Asia, is probably explained by the origin of R. rattus, which is native to the Indian Peninsula, and has been introduced to Madagascar, through the Arabic Peninsula, about 2000-3000 years ago on the coast, and later in the highlands, with the arrival of the first human migrants and the colonization of the island (Tollenaere et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Phylogenetic characterization based on nucleotide sequences of the partial S segment of SEOV isolated in South East Asian countries including Cambodia [18] and Singapore [6] indicated that they formed one South East Asian virus lineage. Our previous study on phylogenetic characterization of many SEOVs isolated in China, Japan, Korea and U.S.A. showed that they were divided into 5 closely related subgroups within one clade and that viruses in one subgroup seemed to have migrated to East Asian countries and U.S.A. [23].…”
Section: Discussionmentioning
confidence: 99%
“…1). Species of animals were determined first by morphological characteristics, and then mitochondrial DNA sequencing was carried out in representative animals as previously described [18].…”
Section: Viral Strains and Cellsmentioning
confidence: 99%
“…Despite the close associations between rodent hosts and hantaviruses, exceptional host switching and spillover cases have been reported [26,27]. Recent studies have shown that R. tanezumi in Indonesia and R. rattus in Cambodia possessed THAIV-like hantaviruses [20,21]. Furthermore, prevalence of a novel HTNV was reported among laboratory rats (Rattus norvegicus) in China [30].…”
mentioning
confidence: 99%